Peran Petugas Kesehatan dan Keluarga terhadap Self Care Penderita Kusta - Mujib Hannan; Syaifurrahman Hidayat; Mayank Nirmala Sandi (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2020)
ABSTRACT An infectious disease that is still found in Indonesian society, namely leprosy, Indonesia ranks third in the world after Brazil. East Java is in the first place with the highest number of new cases of leprosy in 2018, with 2,701 people. Individual self care is influenced by age, gender, developmental status, health status, socio-culture, health services, family system, lifestyle, environment, and availability of resources. The purpose of this study was to determine the role of health workers and families in self-care for people with leprosy in Batuputih District, Sumenep Regency. Analytical research design with cross sectional design. The population is people with leprosy in Batuputih Health Center. The sampling technique was purposive sampling with a sample of 32 respondents. Statistical test using the Spearman correlation test. The results of the study of 25 respondents obtained that most of the health workers participated in the self-care of leprosy sufferers as many as 16 people (64.0%), most of the families did not play a role in self-care for people with leprosy as many as 15 people (60.0%), almost all of them were self-care. care in the less category as many as 20 people (80.0%), there is no relationship between the role of health workers and self-care for people with leprosy with Sig. 0.065 (> 0.05) and there is a relationship between family roles and self-care for lepers with Sig. 0.001 (<0.05) in Batuputih Sumenep District with the results of the Spearman test. Families who do not play a role cause bad self-care for people with leprosy so that this can increase the risk of disability and worsen the condition of lepers. The role of health workers and families who are active in supporting self-care for people with leprosy can facilitate the healing and recovery process for people with leprosy and as a step to reduce the spread of leprosy. Keyword: Leprosy, Role of Health Workers, Family Role, Self Care